Development of Four-Tier Instrument at First Intermediate Level Chemistry Concepts - Wijayadi, Andri Wahyu; Fitriyah, Lina Arifah; Manasikana, Oktaffi Arinna (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
Chemical concepts are tiered from simple to complex. If misconceptions occur in simple concepts, they can cause misconceptions in complex concepts. The four-tier instrument is a tool for detecting misconceptions. This research aims to develop and describe the validity and reliability of a four-tier instrument on junior secondary-level chemistry concepts. This development research consists of 6 procedures: (1) concept mapping, (2) testing, (3) defining unscientific concepts, (4) developing four-tier instrument prototypes, (5) validating four-tier instrument prototypes, and (6) finalization of four-tier instruments. The developed four-tier instrument consists of 27 questions that measure chemistry concepts at the junior intermediate level. The instrument received an expert validation score of 92.81% with very valid criteria. The test results on 30 samples showed a reliability value based on a Cronbach alpha score of 0.713 with good criteria. The four-tier instrument on lower secondary level chemistry concepts meets the validity and reliability requirements so that it can be used to diagnose misconceptions on lower secondary level chemistry concepts.